179 Evaluating a Clinical Pharmacist Service in a Residential Care Unit. (16th September 2019) - Kavanagh, Claire; O'Dwyer, Eimear; Purcell, Róisín; McMahon, Niamh; Crowe, Morgan; Scott, Michael
Abstract: Background: This study assessed the pharmacist role in an 80 bed residential care unit by: Quantifying the number and type of pharmacist interventions made and their acceptance rate. Assessing impact of pharmacist interventions on patient care. Assessing staff attitudes towards the clinical pharmacist service. Methods: This was a non-blinded, non-comparative evaluation of the existing clinical pharmacist service in the unit. All residents were included. All pharmacist interventions over a 10-week period were recorded, then graded according to the Eadon scale 1 by a consultant gerontologist and an experienced pharmacist to assess their impact on patient care. Results: There were 615 pharmacist interventions. The most common interventions were: Drug Therapy Review, 34% (n=209) Technical Prescription, 26.5% (n=163) Administration, 15.3% (n=94) Drug Interaction, 10.4% (n=64) Medication Reconciliation, 8.5% (n=52) 98% (n=596) of interventions were rated as having significance to patient care, of which: 48.4% (n=298) and 41.8% (n=257) of the interventions rated as 'significant and resulting in an improvement in the standard of care' 1% (n=6) and 0.5% (n=3) rated as 'very significant and preventing harm'. There was a statistically significant agreement between the evaluators, κw = 0.231 (95% CI, 0.156 to 0.307), p < .0005. The strength of agreement was fair. Of interventions requiring acceptance by medical team (n=335), 89.9% (n=301) were accepted. 95% (n=36) of staff who responded agreed or strongly agreed that improved patient safety resulted from the pharmacist's involvement in multidisciplinary medication reviews. Over 92% (n=35) agreed or strongly agreed that their experience of the pharmacist was positive. Conclusion: The pharmacist has an important role in our residential care unit. Their involvement in the medicines optimisation process positively impacts patient outcomes and prevents harm. Staff perceived a positive impact of the clinical pharmacist service provided on patient care and patient safety.